Block Chain-based Adjustable Electricity Resource Transaction Process and Clearing Model - Zhou, Xia; Dang, Wei (Procedia computer science, 2025)
The integration and participation in system regulation of adjustable load resources including electric vehicle and user side energy storage can relieve the electricity supply and demand contradiction, promote the new energy consumption, reduce the system construction and operating cost and improve the social energy efficiency level. This paper presents a method of using the block chain technology to provide transaction clearing for aggregators and adjustable resources. The method builds a double-layer optimal scheduling model aiming at the cost optimization, of which the upper layer is used for the transaction between aggregators and distribution network operators, and the lower layer considers response mode, scheduling potential and scheduling cost of different resources and other factors. This method also establishes the judgment method of resource scheduling priority and the comprehensive evaluation of resources in terms of price, credit and response speed. The model can support the safe and reliable transaction between power distribution network and adjustable resources.